2023
DOI: 10.1093/burnst/tkad029
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and mitophagy: crucial players in burn trauma and wound healing

Abstract: Burn injuries are a significant cause of death worldwide, leading to systemic inflammation, multiple organ failure and sepsis. The progression of burn injury is explicitly correlated with mitochondrial homeostasis, which is disrupted by the hyperinflammation induced by burn injury, leading to mitochondrial dysfunction and cell death. Mitophagy plays a crucial role in maintaining cellular homeostasis by selectively removing damaged mitochondria. A growing body of evidence from various disease models suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…Lastly, a 2023 review article detailed the correlation of burn injury progression with mitochondrial homeostasis, which is mediated via burn injury-induced hyperinflammation and subsequent mitochondrial dysfunction and cell death [ 50 ]. As mitophagy maintains cellular homeostasis by the selective removal of damaged mitochondria, the authors suggested that the process of mitophagy could be a promising therapeutic strategy for wound healing and burn injury.…”
Section: Mitochondria Dysfunction and Dermatological Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, a 2023 review article detailed the correlation of burn injury progression with mitochondrial homeostasis, which is mediated via burn injury-induced hyperinflammation and subsequent mitochondrial dysfunction and cell death [ 50 ]. As mitophagy maintains cellular homeostasis by the selective removal of damaged mitochondria, the authors suggested that the process of mitophagy could be a promising therapeutic strategy for wound healing and burn injury.…”
Section: Mitochondria Dysfunction and Dermatological Manifestationsmentioning
confidence: 99%
“…As mitophagy maintains cellular homeostasis by the selective removal of damaged mitochondria, the authors suggested that the process of mitophagy could be a promising therapeutic strategy for wound healing and burn injury. Furthermore, the authors discuss Pink1 and Parkin activators and USP30 inhibitors as potential therapeutic agents for the regulation of mitophagy and the subsequent mitigation of burn injury progression [ 50 ].…”
Section: Mitochondria Dysfunction and Dermatological Manifestationsmentioning
confidence: 99%